Introduction to chemical exposure and risk assessment - Neely,W. Brock (Lewis Publishers, 1994)
Risk perception.--Statistics.--Mammalian toxicology.--Cancer and carcinogenic chemicals.--The atmosphere.--Water.--Exposure assesment.--Risk benefit analysis.--Case Studies.